Pkm Inseminasi Buatan Dan Budidaya Ayam Kampung Di Kelompok Tani Unggas Jaya, Kefamenanu - Dethan, Agustinus Agung; Lisnahan, Charles Venirius; Joka, Umbu; Nubatonis, Alfred; Nubatonis, Agustinus (LPPM Universitas Timor, 2024)
This activity was carried out using a participatory action research method, namely jointly determining solutions based on the urgency and priority of the problem which was preceded by an initial situation analysis. Furthermore, activities in the field take the form of lectures/counseling, training/demonstrations to improve the group's abilities and skills. The focus of activities is on semen collection, artificial insemination, egg hatching, crumb and pellet making, vaccination, and the starter, grower and pullet maintenance phase and income analysis. Assistance and evaluation of activities is carried out in stages. The impact of this service is an increase in the group's skills in artificial insemination of hens, hatching eggs using a hatching machine, making their own feed in the form of crumbs and pellets, raising chicks in brooding, vaccination, maintaining the grower phase, and being able to analyze business income. At the end of the activity, the partner group can reproduce brood hens for further exposure and development. Group welfare also increases due to additional profits. With a rearing volume of 200 bird, the partner group makes a profit of Rp. 10,240,000 from DOC maintenance until 4-5 months of age.